2020
DOI: 10.1108/jfbm-03-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

Family firms, banks and firm value: Evidence from Malaysia

Abstract: PurposeThis paper examines the relationship between the number of domestic banks that the firm engages with and firm value and how this relationship is moderated by ownership concentration at low and very high level on a sample of Malaysian family and non-family firms.Design/methodology/approachFor hypotheses testing, panel data analysis using the fixed effects model (FEM) is used because the FEM can address any endogeneity problems effectively (Chi, 2005). The panel data regression is conducted on both family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
0
8
0
1
Order By: Relevance
“…Previous research works have used various measures to evaluate the firm value. For example, some researchers used Tobin's Q as the ratio between the firm replacement value (represented by the sum of the firm market value and total debts) and the firm's total assets (Arouri et al , 2014; Enache and Hussainey, 2019; Haj Salem et al , 2020); others use the return on assets (ROA) and/or the return on equity (ROE) as financial accounting performance measures (Liew and Devi, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research works have used various measures to evaluate the firm value. For example, some researchers used Tobin's Q as the ratio between the firm replacement value (represented by the sum of the firm market value and total debts) and the firm's total assets (Arouri et al , 2014; Enache and Hussainey, 2019; Haj Salem et al , 2020); others use the return on assets (ROA) and/or the return on equity (ROE) as financial accounting performance measures (Liew and Devi, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we took into account the activity sector of our sampled financial institutions. According to Liew and Devi (2020) and Abdi et al (2020), firm type is a significant variable as the firm value can be different depending on the type of industry. Thus, we expect that the activity sector will be positively associated with the firm value.…”
Section: Definitions and Measurements Of Study Variablesmentioning
confidence: 99%
“…They are particularly vulnerable because of their autonomy as well as their family-based standing (Lee, 2006). Several researchers (Runyan, 2006;Kraus et al, 2020;Kub ı cek et al, 2021;Liew and Devi, 2021) have observed that a crisis typically affects owners of family businesses twicefirst because they are private citizens and second because they are business owners (Nordqvist and Melin, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2020; Kubíček et al. , 2021; Liew and Devi, 2021) have observed that a crisis typically affects owners of family businesses twice – first because they are private citizens and second because they are business owners (Nordqvist and Melin, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dominant family company shows a higher company risk (Rajverma, 2019). This can lead to conflicts between majority and minority shareholders where family companies tend to ignore minority interests, thereby affecting firm value (Liew, 2020).…”
Section: Ijobpmentioning
confidence: 99%